SCIENTIFIC FOUNDATIONS OF ECONOMIC AND BUSINESS DEVELOPMENT IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT: MODERN CHALLENGES - Erkinbaev M. T.; Myrzakmatova A. S. (Vestnik Issyk-Kulʹskogo universiteta)
The article will examine the main issues related to the economy and sustainable development. The industry is a pear of enterprises offering their products not in one single market, but in different single markets. Sustainable development is a set of measures aimed at satisfying current human needs while preserving the environment and resources, i.e. without compromising the ability of future generations to meet their own needs. Sustainable development is possible with a balance of three main components: economic growth, social responsibility and ecological balance. An industry is wider than a market. Markets unite sellers and buyers of goods and services that are substitutes from the point of view of consumers, and industries unite producers of goods that are substitutes and offered on a single market from the point of view of supply. To determine the economic boundaries of an industry and a market, one can use the concept of a single market that satisfies the same need and has a high price cross-elasticity of demand. A similar conclusion can be made based on an assessment of the correlation of prices over time high the correlation coefficient means high interchangeability of products, which means they form a single market for infocommunications services.